2004
DOI: 10.1063/1.1830687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bi surfactant on atomic ordering of GaAsSb

Abstract: The addition of small quantities of a Bi surfactant is shown to have dramatic effects on the microstructure of GaAsSb alloys grown by organometallic vapor phase epitaxy (OMVPE). Epilayers grown without Bi show weak atomic ordering in plan-view selective area electron diffraction measurements, with periodicity of three or six times the [110] lattice spacing as previously reported. The addition of Bi at a ratio of 1% Bi∕Ga to the gas flow results in the appearance of strong CuAu and chalcopyrite ordering, as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It is worth noting that other authors have seen fairly large discrepancies of up to 0.2 eV in the PL energies compared with predictions obtained using tabulated values of the bowing parameters [15]. We have also performed TEM measurements on these samples, which showed ordering in these quaternary material similar to the Cu-Au type observed in GaAsSb [16,17]. Recent PL measurements on GaAsSb ternary alloys indicated that the presence or absence of strong Cu-Au ordering had no effect on the PL energies [17].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…It is worth noting that other authors have seen fairly large discrepancies of up to 0.2 eV in the PL energies compared with predictions obtained using tabulated values of the bowing parameters [15]. We have also performed TEM measurements on these samples, which showed ordering in these quaternary material similar to the Cu-Au type observed in GaAsSb [16,17]. Recent PL measurements on GaAsSb ternary alloys indicated that the presence or absence of strong Cu-Au ordering had no effect on the PL energies [17].…”
Section: Resultsmentioning
confidence: 78%
“…We have also performed TEM measurements on these samples, which showed ordering in these quaternary material similar to the Cu-Au type observed in GaAsSb [16,17]. Recent PL measurements on GaAsSb ternary alloys indicated that the presence or absence of strong Cu-Au ordering had no effect on the PL energies [17].…”
Section: Resultsmentioning
confidence: 83%
“…We have also observed weak three-fold and six-fold ordering along [1 1 0] which correlates with increased bulk resistivity along the [1 1 0] direction in OMVPE-grown GaAsSb [11]. In a previous paper, we reported that Bi can be used as a surfactant to produce dramatic changes in the ordering microstructure of GaAsSb grown on exact (0 0 1) InP surface by OMVPE [12]. strong CuAu and CH orderings similar to those originally reported in GaAsSb growth on 31 offcut (0 0 1) InP [3].…”
Section: Introductionmentioning
confidence: 67%
“…The effect of Bi surfactant was briefly discussed in an earlier paper [8]. The strongest ordering effects were observed using the SH1 chamber as shown in Fig.…”
Section: Effect Of Bi Surfactantmentioning
confidence: 82%
“…Atomic ordering of III-V semiconductor alloys has been widely studied in the past two decades [1][2][3][4][5][6][7][8]. The most common ordered phase is the so-called CuPt variant in which an alloy compound semiconductor, usually grown by either molecular beam epitaxy (MBE) or metalorganic vapor phase epitaxy (MOVPE), spontaneously forms ordered superlattices aligned along the (111)B planes.…”
Section: Introductionmentioning
confidence: 99%